The project-based learning model and its contribution to student creativity: A review - Rahmadhani Fitri; L. Lufri; Heffi Alberida; Ali Amran; Rifani Fachry (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Currently, students tend to be less innovative and creative in learning and its implementation in everyday life. Project-Based Learning (PjBL) is a learning strategy oriented towards contextual problem solving to find solutions based on the experiences of students so that they can be more creative and innovative. This research aims to reveal how PjBL contributes to increasing student creativity. This research was conducted with a literature review of articles in international journals, international seminar proceedings, and SINTA accredited journals. Based on the results of the analysis carried out, it was found that to realize high creativity, the PjBL model is one of the best solutions to increase students' creativity. This learning model is able to make students more creative and innovative in solving every problem in everyday life by following PjBL syntax. PjBL is suggested to be an alternative for educators to train and foster the formation of students' creativity. It can also be concluded that PjBL can train and increase student creativity because the syntax of this learning model allows students to explore, create, interpret and develop products resulting from their projects.